Enhancing Digital Literacy in Village Government for Effective SID Program Implementation - Rodiyah, Isnaini; Bolanitan, Zeyromita Oversi (Indonesian Journal of Public Policy Review, 2023)
This study investigates digital literacy among village government officials in Kalisogo Tambak during the implementation of the Village Information System (SID) Program. Employing a descriptive analysis with a quantitative approach, data was gathered through observations, interviews, and questionnaires. The research focused on seven aspects of digital literacy, including knowledge assembly, information presentation, material comprehension, awareness of media importance, network access awareness, information filtering, and comfort with communication and information dissemination. Results indicate an overall strong digital literacy index among the village government apparatus, with the highest score in feeling comfortable and having broad access (77%) and the lowest in awareness of the importance of conventional media and its connection to internet media (70%). The findings underscore the need for targeted interventions to improve awareness in this specific aspect, offering valuable insights for enhancing integrated digital-based public services. Highlight : Integrated Digital Services: The study evaluates the digital literacy of Kalisogo Tambak's village government apparatus, providing insights into their proficiency in utilizing the SID Program for delivering integrated digital-based public services. Dimension-specific Insights: Results reveal a notable proficiency in aspects such as feeling comfortable and having a wide range of access, emphasizing the need for tailored interventions to enhance awareness regarding the importance of conventional media and its linkage to internet media. Strategic Improvement Recommendations: The research suggests targeted strategies for improving digital literacy among village officials, aiming to bolster their capabilities and ensure more effective utilization of the SID Program for enhanced public service delivery. Keywords: Digital Literacy, Village Government, SID Program, Information Technology, Public Services